Perceptions and Experiences of a Multimodal Rehabilitation Program for People With Post‐Acute COVID‐19: A Qualitative Study - Beatriz Carpallo‐Porcar; Sandra Calvo; Sara Pérez‐Palomares; Laura Blázquez‐Pérez; Natalia Brandín‐de la Cruz; Carolina Jiménez‐Sánchez (Health Expectations, 2025)
ABSTRACT Introduction Home‑based rehabilitation has emerged as a practical solution for post‑acute phase COVID‑19 recovery, but patient perspectives on the different modalities remain underexplored. Objective To explore participants' perceptions and experiences after a 12‑week multimodal rehabilitation program delivered via asynchronous telerehabilitation versus a booklet after discharge and to identify the preferred format. Methods Qualitative descriptive study with two face‑to‐face focus groups of post‐discharge COVID‐19 patients (n = 12; age range 41–75 years; 50% female; with fatigue > 4 on the Fatigue Severity Scale) that included participants from each intervention arm of a randomised pilot study. Semi‑structured interviews to determine patients' perceptions and experiences were recorded, transcribed verbatim and coded independently by two researchers using inductive thematic analysis. Results Three overarching themes emerged from the analysis: (1) Facilitators for engagement and adherence: Innovative digital tools and personalised guidance foster active participation by providing flexible access and systematic progress monitoring; (2) Barriers to sustained participation: Technological issues, physical limitations and fluctuating motivation serve as critical impediments, underscoring the potential benefits of hybrid intervention models; and (3) Therapeutic alliance as support: A robust, individualised therapeutic relationship enhances patient confidence and self‐management, ultimately contributing to sustained empowerment and recovery. Conclusions A multimodal home‐based rehabilitation program with monitoring and personalisation by the physiotherapist is rated positively by post‐acute COVID‐19 patients, with asynchronous telerehabilitation emerging as the preferred method. Future research should investigate long‑term adherence, clinical efficacy and scalability. Clinical Trial Registration Clinialtrials.gov #NCT04794036. Patient or Public Contribution Post‐acute COVID‐19 patients contributed to the study by actively participating in its development, specifically through describing their experiences as part of a multimodal rehabilitation program. There was no additional participation or contribution from the public to the research.